Interreligious Engagement and Identity Theory: Assessing the Theology of Religions Typology as a Model for Dialogue and Encounter - Hedges, Paul (Journal for the academic study of religion, 2014)
This paper will use identity theories developed in sociology, social psychology and cognate areas to assess traditional Christian theories about religious Others. Employing the theology of religions typology as a focus, it will be argued that Christian theological approaches tend to stress monolithic notions of identity and are not adequate as tools to approach religious Others. Even where more nuanced understandings of identity are employed it is argued that these tend to be very generic and speak broadly of identity' without classifying what is meant, for instance, by group' or personal', and so discussions tend to be inadequate. It will further be suggested that certain theological positions are inherently problematic with regards to engaging Others when viewed through the lens of identity theories, and possible ways forward are suggested. This paper is an attempt to explore the territory of identity theory in this area and is intended to promote further research.